Snail promotes cell migration through PI3K/AKT-dependent Rac1 activation as well as PI3K/AKT-independent pathways during prostate cancer progression - Henderson, Veronica (Cell Adh Migr, 2015)
Snail, a zinc-finger transcription factor, induces epithelial-mesenchymal transition (EMT), which is associated with increased cell migration and metastasis in cancer cells. Rac1 is a small G-protein which upon activation results in formation of lamellipodia, the first protrusions formed by migrating cells. We have previously shown that Snail promotes cell migration through down-regulation of maspin tumor suppressor. We hypothesized that Snail's regulation of cell migration may also involve Rac1 signaling regulated by PI3K/AKT and/or MAPK pathways. We found that Snail overexpression in LNCaP and 22Rv1 prostate cancer cells increased Rac1 activity associated with increased cell migration, and the Rac1 inhibitor, NSC23766, could inhibit Snail-mediated cell migration. Conversely, Snail downregulation using shRNA in the aggressive C4–2 prostate cancer cells decreased Rac1 activity and cell migration. Moreover, Snail overexpression increased ERK and PI3K/AKT activity in 22Rv1 prostate cancer cells. Treatment of Snail-overexpressing 22Rv1 cells with LY294002, PI3K/AKT inhibitor or U0126, MEK inhibitor, decreased cell migration significantly, but only LY294002 significantly reduced Rac1 activity, suggesting that Snail promotes Rac1 activation via the PI3K/AKT pathway. Furthermore, 22Rv1 cells overexpressing Snail displayed decreased maspin levels, while inhibition of maspin expression in 22Rv1 cells with siRNA, led to increased PI3K/AKT, Rac1 activity and cell migration, without affecting ERK activity, suggesting that maspin is upstream of PI3K/AKT. Overall, we have dissected signaling pathways by which Snail may promote cell migration through MAPK signaling or alternatively through PI3K/AKT-Rac1 signaling that involves Snail inhibition of maspin tumor suppressor. This may contribute to prostate cancer progression.